2011
DOI: 10.1021/ja111731d
|View full text |Cite
|
Sign up to set email alerts
|

Combining Aryltriazenes and Electrogenerated Acids To Create Well-Defined Aryl-Tethered Films and Patterns on Surfaces

Abstract: Immobilization of submonolayers to 4-5 multilayers of organic molecules on carbon surfaces can be performed by in situ generation of aryl radicals from aryltriazenes. The central idea consists of oxidatively forming an electrogenerated acid of N,N'-diphenylhydrazine to convert the aryltriazene to the corresponding diazonium salt in the diffusion layer of the electrode. In a second step, the diazonium salt is reduced at the same electrode to give a surface of covalently attached aryl groups. In this manner, var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
42
0
1

Year Published

2011
2011
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 24 publications
(43 reference statements)
4
42
0
1
Order By: Relevance
“…Thus, the ''one pot'' procedure, under optimized conditions, can be approximated to the sum of quantitative steps that mimic well the sequential procedure in a thin solution layer against the electrode surface. Since, this original procedure is promising for the local production of diazonium salts from nitro precursors and allows reconsidering the use of diazonium salts for microelectrochemical patterning of surfaces by application of the scanning electrochemical microscopy [28,[43][44][45].…”
Section: E (V)mentioning
confidence: 99%
“…Thus, the ''one pot'' procedure, under optimized conditions, can be approximated to the sum of quantitative steps that mimic well the sequential procedure in a thin solution layer against the electrode surface. Since, this original procedure is promising for the local production of diazonium salts from nitro precursors and allows reconsidering the use of diazonium salts for microelectrochemical patterning of surfaces by application of the scanning electrochemical microscopy [28,[43][44][45].…”
Section: E (V)mentioning
confidence: 99%
“…[2] Other probe-generated reagents include metal ions for metal deposition, [9,10] catalytically active metal ions, [11] and aryl diazonium salts. [6,12] The pH shift associated with nitrite oxidation was applied in the local etching of a thin Ni coating on a gold substrate in a chemical lens. [13] Kanoufi et al reported the localized reduction of poly(tetrafluoroethylene) [14] and the oxidation of polystyrene [15] followed by further surface treatments.…”
mentioning
confidence: 99%
“…The amount of unreacted C À Br within a pattern, q CÀBr (Figure 2 f), was attested from their engagement in growth of polymer brushes by ATRP and shown by local ellipsometric measurement (see the Supporting Information). It should be possible to scrutinize a wide range of organic, [16,21,22] organometallic, [23] or inorganic [24] chemical reactions, which is a fundamental issue to assist in the rational selection of conditions for surface or material synthesis. For a linear activation-driving force variation, the C À Br reductive transformation is associated to a transfer coefficient a = RT dln(k etch )/FdE 0 = 0.18, in favor to a large reorganization, as in bond-dissociative ET.…”
mentioning
confidence: 99%
“…It is even not restricted to redox reagents owing to the chemical diversity that can be generated by SECM electrochemical activation or by a SICM micropipette delivering system. It should be possible to scrutinize a wide range of organic, [16,21,22] organometallic, [23] or inorganic [24] chemical reactions, which is a fundamental issue to assist in the rational selection of conditions for surface or material synthesis.…”
mentioning
confidence: 99%